2019
DOI: 10.1111/jop.12851
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of BRAF V600E mutations in Korean patients with ameloblastoma: Clinicopathological significance and correlation with epithelial‐mesenchymal transition

Abstract: Background BRAF V600E mutations are activating mutations that have recently been detected in ameloblastoma. However, their prevalence has not been reported in East Asian patients with ameloblastoma and their clinicopathological significance remains unclear. In this study, we examined the prevalence and clinicopathological significance of BRAF V600E mutations in Korean patients with ameloblastoma. In addition, we investigated the relationship between BRAF V600E mutations and epithelial‐mesenchymal transition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 28 publications
3
42
2
Order By: Relevance
“…In our study, 97% of ameloblastomas—all but one case—occurred in the mandible. The BRAF V600E mutation is most common genetic alteration in ameloblastoma, and its frequency varied from 43% to 90% in previous studies 12–20 . Mutation of SMO is also seen in 82% of maxillary ameloblastoma; it is most common genetic event in ameloblastomas that develop in the maxilla 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, 97% of ameloblastomas—all but one case—occurred in the mandible. The BRAF V600E mutation is most common genetic alteration in ameloblastoma, and its frequency varied from 43% to 90% in previous studies 12–20 . Mutation of SMO is also seen in 82% of maxillary ameloblastoma; it is most common genetic event in ameloblastomas that develop in the maxilla 12 .…”
Section: Discussionmentioning
confidence: 99%
“…reported that 47% of ameloblastoma was IHC‐positive for BRAF V600E antibody. When BRAF V600E IHC expression and BRAF gene mutations were compared, 63%, 19 66% 13 and 73 % 14 of IHC‐positive cases reportedly had BRAF mutations. In our study, 69% (22/32) of total ameloblastoma cases showed positive BRAF V600E IHC staining, and 73% (16/22) of the positive cases had BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BRAF V600E mutation is the most common oncogenic mutation in the BRAF gene, which induces constitutive activation of the mitogen‐activated protein kinase (MAPK) pathway. BRAF V600E mutations are frequently found in melanoma, 1 thyroid cancer, 2 and colorectal cancer 3 and have also been detected in ameloblastoma, a clinically significant and locally invasive odontogenic tumour, through the use of molecular tests 4‐9 . Other odontogenic tumours presenting with ameloblastic epithelium, including ameloblastic carcinoma (AC), ameloblastic fibroma (AF), ameloblastic fibro‐odontoma (AFO), ameloblastic fibro‐dentinoma (AFD) and ameloblastic fibrosarcoma (AFS), have been reported to have the mutation 4‐6,10 …”
Section: Introductionmentioning
confidence: 99%
“…An additional level of action of SOX2 is promotion of tumor aggressiveness and the process of epithelial‑mesenchymal transition (EMT) in several types of cancers, like in tongue squamous cell carcinoma 27 . Initial evidence for occurrence of EMT in AMB 28,29 and also in OKC 30 has been reported; however, the involvement of SOX2 in this setting remains to be clarified and related to the differential expression that we have found between the stroma of odontogenic tumors and cysts. Therapeutically, several strategies that have recently been described targeting SOX2, 31 further justify this investigation.…”
Section: Discussionmentioning
confidence: 82%